Efektifitas Edukasi Kesehatan dalam Peningkatan Efikasi Diri Lansia dengan Hipertensi Selama Vaksinasi Covid-19 - Agnes Dewi Astuti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The elderly are one of the targets of the Covid-19 vaccination and are a vulnerable group with health problems, such as hypertension. Hypertension can cause failure in the process of administering vaccines which has an impact on low self-efficacy for the elderly, due to the inability to overcome these problems. The purpose of this study was to determine the effectiveness of health education to increase the efficacy of elderly people with hypertension during the Covid-19 vaccination. The research design was one group pretest-posttest. The research sample was 32 elderly people with hypertension in the working area of the Kayon Health Center, who were taken using a purposive sampling technique. The elderly were given health education and discussion about the Covid-19 vaccine and self-efficacy assessment was carried out using the General Self Efficacy Scale (GSES) questionnaire. The results were analyzed using a paired sample t-test showing that the value of p = 0.000, so it could be interpreted that there was a difference in self-efficacy between before and after the treatment. It was concluded that health education is effective in increasing the efficacy of elderly people with hypertension during the Covid-19 vaccination.Keywords: education; elderly self-efficacy; Covid-19 vaccination ABSTRAK  Lansia merupakan salah satu sasaran vaksinasi Covid-19 dan merupakan kelompok rentan dengan masalah kesehatan, seperti hipertensi. Hipertensi dapat menyebabkan kegagalan dalam proses pemberian vaksin yang berdampak pada rendahnya efikasi diri lansia, karena ketidakmampuan mengatasi masalah tersebut. Tujuan penelitian ini adalah untuk mengetahui efektifitas pendidikan kesehatan untuk meningkatkan efikasi lansia penderita hipertensi selama vaksinasi Covid-19. Rancangan penelitian ini adalah one group pretest-posttest. Sampel penelitian adalah 32 lansia penderita hipertensi di wilayah kerja Puskesmas Kayon, yang diambil dengan teknik purposive sampling. Lansia diberikan edukasi kesehatan dan diskusi tentang vaksin Covid-19 dan penilaian efikasi diri dilakukan dengan menggunakan kuesioner General Self Efficacy Scale (GSES). Hasil dianalisis dengan menggunakan paired sampel t-test menunjukkan bahwa nilai p = 0,000, sehingga dapat diinterpretasikan bahwa ada perbedaan efikasi diri antara sebelum dan sesudah pemberian perlakuan. Disimpulkan bahwa pendidikan kesehatan efektif untuk meningkatkan efikasi lansia penderita hipertensi selama vaksinasi Covid-19.Kata kunci: pendidikan; efikasi diri lansua; vaksinasi Covid-19